Potensi Pemanfaatan Digitalisasi Sebagai Strategi Pengembangan UMKM Keripik Pisang Sale di Desa Sumber Datar - Ismandianto I; Tugiran T; Esti Yuati Putri; Rizky Kurnia Ananda; Aisyah Kusumo Dewi; Wahyu Hidayah; Sucitra Lestari Lubis; Alfina Dawanni; Sunse Ayu Febriani; Viola Egis Pratiwi; Habil Arianda Putra (Yayasan Daarul Huda Kruengmane, 2023)
This dedication article focuses on the activities of the Sumber Datar Kukerta Team's service related to the use of digitalization as a marketing development strategy and know the efficiency of the Sale Banana Chips business in Sumber Datar Village. This Small and Medium Enterprise (SME) is a processed product from bananas developed in Singingi District. This is supported by abundant banana production in Sumber Datar Village. This dedication activity is interesting to study because with the business activities of the Salean Sale Chips Food Processing can contribute to profits for the surrounding area business actors. This is supported by the use of marketing digitalization which plays an important role in the sales process that reaches targets to foreign countries such as Malaysia. This service article uses a qualitative approach which includes three stages, namely observation, socialization, and implementation. The results showed that the socialization activity of MSMEs of Sale Mbok Ikem banana chips had been carried out with the output of a MSME marketing content as well as information related to the use of digitalization through social media as a marketing forum.